Gamification in university students learning - Vélez Osorio, Iris María (Rastros Rostros, 2016)
Introduction: the purpose of this article is to describe gamification as a new teaching-learning methodology, which allows students to meet specific learning objectives and develop skills. Methodology: a qualitative and quantitative analysis was carried out, observing two groups, one which received traditional class methodology whilst the other received a gamification methodology for the same subject. Observation was complemented by a numerical analysis of their academic performance. Results: this study presents a comparison between the gamification and the traditional class methodology to know their effects on students’ motivation. Conclusions: it is concluded that gamification positively affects the learning process since it stimulates motivation in students, particularly due to the positive interaction between teacher and students.